Pengaruh Komitmen Organisasi dan Persepsi Lingkungan Kerja Terhadap Turnover Intention dengan Kepuasan Kerja Sebagai Variabel Intervening pada Karyawan PT Global JNT Cargo Semarang - Khoerunnisa Awaliyatul Khanifah; Hardani Widhiastuti; Rusmalia Dewi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research analyzes the influence of organizational commitment and work environment perception on turnover intention, with job satisfaction as an intervening variable among employees of PT Global JNT Cargo Semarang. High employee turnover intention motivated this research, with the assumption that low organizational commitment and a poor work environment perception are contributing factors. Job satisfaction is hypothesized to mediate this relationship. A quantitative method with a Partial Least Square (PLS) approach was used. Data were collected through questionnaires distributed to employees of PT Global JNT Cargo Semarang using a purposive sampling technique. Data analysis was performed using SmartPLS for validity, reliability, and hypothesis testing. The results show that organizational commitment has a negative and significant effect on turnover intention. However, work environment perception has a positive and significant effect on turnover intention (this finding needs to be revisited). Job satisfaction partially mediates the influence of organizational commitment and work environment perception on turnover intention. This means that good organizational commitment and work environment perception can increase job satisfaction and reduce turnover intention. This research implies the need to improve organizational commitment and create a positive work environment to reduce turnover intention through increased job satisfaction.